Acculturation-Related Factors of Dietary Pattern Changes among Indigenous Adolescents in Mt. Arayat, Philippines - Barcena, Mark Spencer K.; Orillo, Anna Teresa O.; Juanico, Clarissa B.; Tuaño, Arvin Paul P. (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2021)
This study aimed to determine the levels of dietary acculturation and factors affecting acculturationrelated changes in dietary patterns of 15 adolescents in an indigenous community in Mt. Arayat, Central Luzon, Philippines displaced after the eruption of Mt. Pinatubo in 1991. Mixed-methods sequential explanatory design (using modified scales) was employed to measure dietary acculturation; index analyses to evaluate dietary patterns; and focus group discussion to determine factors leading to dietary acculturation. Majority was found to be bicultural (93.33%) and the mean dietary pattern index score was 69.40 implying a need for dietary improvement. Moderate to high levels of dietary acculturation were observed on the traditional food block, while low to moderate levels were observed towards the dominant food block. Various psychosocial factors driving dietary choices cumulatively affect dietary patterns of adolescents experiencing acculturation in this study, including but not limited to: 1) the neighboring communities’ ethnocultural composition facilitates acculturation primarily through language fluency; 2) prevalence of discrimination exerts an external pressure to adopt host culture for social acceptance; 3) economic need for integration to sustain day-to-day activities exists; 4) religious feasts and gatherings centered on foods previously unknown to them have been introduced; 5) food selection behavior shifts due to acquired experiences of food whether sensory or cognitive; and 6) their attitudes towards assimilation majorly characterizes the gradual internalization of host culture.